Tabarruj Perspektif Wahbah Az-Zuhaili dalam Tafsir Al-Munir - Nabila Fajriyanti Muhyin; Moh. Jufriyadi Sholeh (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
Tabarruj is the behavior of a woman who always looks luxurious and shows her jewelry and beauty to others, which in general these jewelry will not be shown by a good woman, or even wear something that is not natural to wear. This study discusses the meaning of tabarruj in the Qur'an according to contemporary commentators, namely Wahbah Az-Zuhaili in his commentary book Tafsir al-Muni>r. The purpose of this study is to analyze how the interpretation of the verses about tabarruj and what are the forms of tabarruj according to Wahbah Az-Zuh}aili> in Tafsir al-Muni>r. This study uses a literature review with a qualitative approach technique. descriptive analysis. The results of this study indicate that: (1) Wahbah Az-Zuh}aili agrees in interpreting the verses of tabarruj, which is an act of women who display their jewelry to attract the attention of other people who are not their relatives. (2) Wahbah Az-Zuh}aili in his commentary explains several forms of tabarruj actions, including a woman stomping her feet when walking, using excessive perfume, make-up, and jewelry when leaving the house, and wearing tight or revealing clothes.